Hurricane sedimentation in a subtropical salt marsh-mangrove community is unaffected by vegetation type. (5th July 2020) - McKee, Karen L.; Mendelssohn, Irving A.; Hester, Mark W.
Abstract: Hurricanes periodically deliver sediment to coastal wetlands, such as those in the Mississippi River Delta Complex (MRDC), slowing elevation loss and improving resilience to sea-level rise. However, the amount of hurricane sediment deposited and retained in a wetland may vary depending on the dominant vegetation. In the subtropical climate of the MRDC, the black mangrove ( Avicennia germinans ) has been expanding and replacing salt marsh ( Spartina alterniflora ). Because these vegetation types differ in structure, their influence on sedimentation may also differ. We conducted a survey along 160 km of coastline to determine if the spatial deposition pattern in saline wetlands by Hurricanes Gustav and Ike in September 2008 was differentially influenced by vegetation type. Sampling was initiated two months after landfall at eighteen sites in the MRDC containing side-by-side stands of A. germinans and S. alterniflora along the shoreline, with S. alterniflora marsh landward. Average thickness of hurricane sediment across sites varied from 0.6 to 5.6 cm with an overall mean of 2.6 ± 0.4 cm. Within sites, hurricane-layer thickness varied from 1.3 cm at the shoreline to 4.8 cm in the marsh interior, but this pattern was unaffected by vegetation type. Despite greater canopy height, stem density (including pneumatophores), and leaf area, mangroves did not capture more hurricane sediment than salt marsh nor did they attenuate the delivery of sediment to the marsh interior. Data recorded at thirty-six monitoring stations in Louisiana's Coastwide Reference Monitoring System further showed that rates of accretion, as well as elevation change, in saline wetlands ( S. alterniflora ) of the MRDC were temporarily increased by Hurricanes Gustav and Ike. These findings agree with previous work showing the beneficial effects of hurricane sediments on coastal wetlands, but suggest that a climate-driven shift from S. alterniflora to A. germinans in the MRDC will not necessarily alter hurricane sediment capture. Highlights: Hurricanes delivered sediment to Mississippi River Delta subsiding wetlands. Rates of accretion and elevation gain increased in saline wetlands coastwide. More sediment was deposited in interior (low elevation) marshes than shorelines. Aboveground structure of mangrove and salt marsh vegetation differed. Vegetation type, however, did not affect sediment deposition patterns.